Our Transgenic Future : Spider Goats, Genetic Modification, and the Will to Change Nature - Moore, Lisa Jean (New York University Press, 2022)
How scientific advances in genetic modification will fundamentally change the natural worldThe process of manipulating the genetic material of one animal to include the DNA of another creates a new transgenic organism. Several animals, notably goats, mice, sheep, and cattle are now genetically modified in this way. In Our Transgenic Future, Lisa Jean Moore wonders what such scientific advances portend. Will the natural world become so modified that it ceases to exist? After turning species into hybrids, can we ever get back to the original, or are they forever lost? Does genetic manipulation make better lives possible, and if so, for whom?Moore centers the story on goats that have been engineered by the US military and civilian scientists using the DNA of spiders. The goat's milk contains a spider-silk protein fiber; it can be spun into ultra-strong fabric that can be used to manufacture lightweight military body armor. Researchers also hope the transgenically produced spider silk will revolutionize medicine with biocompatible medical inserts such as prosthetics and bandages. Based on in-depth research with spiders in Florida and transgenic goats in Utah, Our Transgenic Future focuses on how these spidergoats came into existence, the researchers who maintain them, the funders who have made their lives possible, and how they fit into the larger science of transgenics and synthetics. This book is a fascinating story about the possibilities of science and the likely futures that may come.